Comparative Aphid Transmission of a Common Citrus Tristeza Virus Isolate and a Seedling Yellows Isolate Recently Introduced into Spain - Hermoso-De-Mendoza, Alfonso; Ballester-Olmos, José F.; Pina, José A. (IOCV, 2021)
Comparative tests of transmission efficiency have been performed using various aphid species and T-300, an isolate of citrus tristeza virus (CTV) widely distributed in Spain, and T-387 a seedling yellows tristeza isolate (CTV-SY) recently introduced into this country. The aphid species tested were those most abundant on citrus in Spain; Aphis citricola, Toxoptera aurantii, Myzus persicae, and Aphis gossypii. A minimum of 200 aphids were used for each test plant. Sweet orange was used as a donor and Mexican lime as a receptor. Aphis gossypi transmitted T-387 with lower efficiency (60%) than T-300 CTV (90%). A. citricola transmitted the two isolates with a very low efficiency. No transmission was observed with T. aurantii or M. persicae.